PO131 Sarcoid myelitis with a striking mri appearance: a case report. (1st December 2017) - Vadukul, Prakash; Fazal, Jawad; Hejmadi, Rahul; Hassan-Smith, Zaki; Hayton, Tom; Williams, Adrian
Abstract : The case presented here is of a patient with longitudinally extensive transverse myelitis (LETM) due to neurosarcoidosis with very striking MRI appearances. Recognition of the MRI findings that strongly support a diagnosis of neurosarcoidosis may facilitate diagnosis and promote early treatment. A previously well, 29-year-old, UK born, Afro-Caribbean man presented with orchitis and a progressive mild tetraparesis with a high cervical sensory level. MRI revealed LETM from C2-C6 with avid 'nodular' enhancement. CSF was normal. Chest imaging revealed hilar lymphadenopathy. Serum ACE was markedly elevated at 180 U/L. Mediastinal node biopsy demonstrated necrotising granulomas. Institution of corticosteroids led to symptomatic improvement with follow-up planned to consider steroid-sparing strategies. Neurosarcoidosis can be challenging to diagnose. The gold standard test is histology but, where sarcoidosis is restricted to the central nervous system, obtaining tissue without risking permanent neurological impairment can be difficult. Recognising characteristic imaging features such as nodular or 'trident' enhancement can help distinguish neurosarcoid from other cuases of LETM.